1999
DOI: 10.1002/(sici)1097-0215(19990315)80:6<823::aid-ijc5>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of BRCA1 protein in sporadic breast carcinoma with or without loss of heterozygosity of the BRCA1 gene

Abstract: In sporadic breast cancer, no mutations of the BRCA1 gene have been reported so far, whereas BRCA1 mRNA is markedly decreased in invasive breast cancer. To elucidate the contribution of the BRCA1 gene in sporadic breast cancer, we quantified the BRCA1 protein, using [ 125 I] labeling of wholecell proteins, lentil-lectin affinity chromatography, immunoprecitation by anti-BRCA1 antibodies (C-20, D-20, I-20 and K-18), purification of the immune complex by protein A affinity chromatography and chromato-focusing. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 0 publications
1
29
1
Order By: Relevance
“…On the other hand, the remaining 90% of breast cancers occur sporadically in the absence of any apparent genetic predisposition. In these nonfamilial cases, tumorigenesis is likely not due to mutation but rather to a drastic decrease of BRCA1 mRNA or protein levels (Magdinier et al, 1998;Rio et al, 1999). Multiple studies have shown a correlation between loss of BRCA1 expression and increased metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the remaining 90% of breast cancers occur sporadically in the absence of any apparent genetic predisposition. In these nonfamilial cases, tumorigenesis is likely not due to mutation but rather to a drastic decrease of BRCA1 mRNA or protein levels (Magdinier et al, 1998;Rio et al, 1999). Multiple studies have shown a correlation between loss of BRCA1 expression and increased metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that BRCA1 mRNA and protein are absent or significantly reduced in 30-40% of sporadic breast cancer cases (Ozcelik et al 1998, Taylor et al 1998, Rio et al 1999, Wilson et al 1999. Decreased BRCA1 expression may be due to hypermethylation of the BRCA1 promoter on CpG islands and/or loss of one of the BRCA1 alleles (Rice et al 1998, Esteller et al 2000, Staff et al 2003.…”
Section: Clinical Research Epidemiology Of Brca1 Mutant Cancersmentioning
confidence: 99%
“…Recent studies indicated that allelic loss in the aforementioned regions might be associated with clinicopathological features of breast cancer. Statistically significant differences between breast tumors with and without LOH in the RAD51 and BRCA1 regions have been found with respect to estrogen receptor content, progesterone receptor content, higher grade, and stage [56,65,66]. Johnson et al [62] detected allelic loss of BRCA1 with higher frequency in women under 36 compared to postmenopausal patients.…”
Section: Discussionmentioning
confidence: 99%